Targeted dual biologic therapy for erythroderma of unknown etiology guided by high-parameter peripheral blood immunophenotyping - Hannah L. Cornman; Martin P. Alphonse; Arbor Dykema; Alexander L. Kollhoff; Kevin K. Lee; Jaya Manjunath; Emily Z Ma; Varsha Parthasarathy; Junwen Deng; Thomas Pritchard; Anusha Kambala; Melika Marani; et al. (Scientific Reports)
Abstract Erythroderma is a severe and heterogeneous inflammatory skin condition with little guidance on the approach to management in cases of unknown etiology. To guide therapeutic selection, we sought to create an immunophenotyping platform able to identify aberrant cell populations and cytokines in subtypes of erythroderma. We performed high-parameter flow cytometry on peripheral blood mononuclear cells (PBMCs) and whole blood of a patient with refractory idiopathic erythroderma, erythrodermic patients with Sézary syndrome and pityriasis rubra pilaris, and healthy controls. We found that the index patient had a novel form of erythroderma characterized by increased interleukin (IL)-13- and IL-17-producing γVδ2 T cells, basophils, and activated platelets. Whole-genome sequencing of PBMCs and immunofluorescence staining of skin biopsies revealed increased expression of Th2- (IL-13, IL-4Rα) and Th17-associated markers (IL-17, IL-17Rα) and non-functional mutations associated with Th2 and Th17 signaling, demonstrating that PBMCs can reflect cutaneous disease pathology. Targeted intervention via dual dupilumab and secukinumab therapy resulted in complete disease control and reduction of immunopathogenic cell populations and cytokines. This study highlights a novel form of erythroderma with concomitant Th2 and Th17 dysregulation and introduces a minimally invasive peripheral blood-based immunophenotyping platform that offers a personalized medicine approach to the management of systemic inflammatory diseases.